DIGITAL-BASED LEARNING MODEL INNOVATION TO ENHANCE UNIVERSITY STUDENTS' CRITICAL THINKING SKILLS: A QUASI-EXPERIMENTAL STUDY - Budi Santoso; Linda Wijaya (DIVERSITY Logic Journal Multidisciplinary, 2026)
Background. The rapid advancement of digital technology has transformed higher education worldwide, requiring innovative instructional approaches that foster higher-order thinking skills. Despite extensive integration of digital technologies in universities, evidence regarding effective digital learning models specifically designed to strengthen students' critical thinking remains limited. Research purpose. This study aimed to develop and evaluate the effectiveness of an innovative digital-based learning model in enhancing university students' critical thinking skills. Research method. A quasi-experimental study employing a pretest-posttest control group design was conducted among 60 undergraduate students enrolled at a higher education. The intervention group (n=30) received instruction through an innovative digital-based learning model integrating collaborative online learning, interactive multimedia, problem-based activities, and reflective discussion. The control group (n=30) received conventional classroom instruction. Critical thinking skills were measured using a validated critical thinking questionnaire and observational assessment sheets. Data were analyzed using descriptive statistics, paired t-tests, and independent t-tests with a significance level of p < 0.05. Findings. The significant improvement in critical thinking scores among students exposed to the digital-based learning model (pretest mean = 64.23 ± 8.14; posttest mean = 81.57 ± 7.26; p < 0.001). The control group also demonstrated improvement, although the increase was substantially lower (pretest mean = 63.80 ± 7.91; posttest mean = 69.43 ± 8.02; p = 0.041). Post-intervention comparisons indicated significant differences between groups (p < 0.001). Conclusion. The innovative digital-based learning model effectively enhanced university students' critical thinking skills by integrating digital technologies with active and collaborative pedagogical strategies.